ANALISIS LAPORAN KEUANGAN DALAM MENGUKUR KINERJA KEUANGAN PADA KOPERASI UNIT DESA (KUD) INTIGRASI KARYA MAKMUR DI DESA KEPENUHAN BARAT KECAMATAN KEPENUHAN KABUPATEN ROKAN HULU - Abu Rizal; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The purpose of this research is to discover financial performance of The Koperasi Unit Desa (KUD) Intigrasi Karya Makmur Kenuhan Barat Village Kepenuhan districts in Rokan Hulu for the year 2014 up to 2018 using analysis of liquidity, solvency and rentability rations. The research method employed in secondary data which data from the financial statements. The data collection techniques that used are observation and documentation method. The data analysis techniques that used are by calculating liquidity, solvency and rentability rations. Based on the financial data analysis of Koperasi Unit Desa (KUD) Intigrasi Karya Makmur the researcher found that the liquidity rate from 2014 up to 2018 as indicated by the current ratio pretty good results and cash ratio gets poor results. The solvency rate from 2014 up to 2018 as indicated by DAR and DER shows very good results. The rentability rate from 2014 up to 2018 as indicated by ROA, ROE and NPM shows very good results. According from the calculating analysis by liquidity, solvency and rentability rations, it said the financial performance of Koperasi Unit Desa (KUD) Intigrasi Karya Makmur needs to be increased again. Keywords: liquidity, solvency and rentability